Recent Development of the Empirical Basis for Prediction of Vortex Induced Vibrations - Larsen, Carl M.; Passano, Elizabeth; Lie, Halvor (ITB Journal Publisher, LPPM ITB, 2016)
This paper describes the research activity related to VIV that has taken place at NTNU and MARINTEK in Trondheim during the last years. The overall aim of the work has been increased understanding of the VIV phenomenon and to improve the empirical basis for prediction of VIV. The work has included experiments with flexible beams in sheared and uniform flow and forced motions of short, rigid cylinders. Key results in terms of hydrodynamic coefficients and analysis procedures have been implemented in the computer program VIVANA, which has resulted in new analysis options and improved hydrodynamic coefficients. Some examples of results are presented, but the main focus of the paper is to give an overview of the work and point out how the new results can be used in order to improve VIV analyses.